Integrative Analysis of the DUF668 Gene Family in Nicotiana tabacum to Excavate Their Potential Roles in Abiotic Stress Responses - Zhenbiao Zhang; Zhongqi Zhang; Sayed Abdul Akher; Jin Xue; Jie Wang; Cun Guo; Zhiyuan Li; Yongfeng Guo (Agronomy, 2024)
The domain of the unknown function (DUF) gene families assumes pivotal roles in plant metabolic and stress responses. However, our comprehension of the tobacco DUF668 (NtDUF668) gene family and its specific reactions to heavy metal, drought, and salt stresses remain circumscribed. In the current investigation, a comprehensive genome-wide analysis of the NtDUF668 gene family was undertaken utilizing bioinformatics tools. The results unveiled a total of 20 members in the NtDUF668 gene family, denominated NtDUF668-01 to NtDUF668-20. Phylogenetic analyses indicated a closer genetic relationship of DUF668 genes between Nicotiana tabacum and Ipomoea batatas. The examination of gene structure and conservative motifs revealed a bifurcation into two major Clades, aligning with previous studies on DUF668 gene families from various plant species, emphasizing its highly conserved evolutionary mechanism across plants. The exploration of promoter regions of NtDUF668 genes revealed a plethora of cis-acting elements associated with abiotic and biotic stresses, light signaling, and phytohormones. Gene duplication events and selection pressure analysis disclosed the segmental duplication and strong purifying selection pressure during the evolution of NtDUF668 genes. Syntenic analysis indicated a relatively conserved evolutionary mechanism of DUF668 gene families within dicotyledons. Tissue-specific expression analysis suggested that NtDUF668 family members are potentially involved in root development, floral organ formation, and abscission. The expression patterns and qRT–PCR analysis of NtDUF668 genes implied the potentially functional involvements of NtDUF668s in response to multiple abiotic stresses. Furthermore, the stress-triggered member NtDUF668-08 exhibited specific nuclear localization. In conclusion, this genome-wide analysis illuminates the composition, phylogenetic relationships, and potential roles of the NtDUF668 gene family in abiotic stress responses. The identified candidate genes, particularly NtDUF668-08, warrant further research for functional investigation.